2019
DOI: 10.2139/ssrn.3479365
|View full text |Cite
|
Sign up to set email alerts
|

Axiomatizations of the Proportional Division Value

Abstract: We present axiomatic characterizations of the proportional division value for TU-games, a value that distributes the worth of the grand coalition in proportion to the stand-alone worths of its members. First, a new proportionality principle, called balanced treatment, is introduced by strengthening Shapley's symmetry axiom, which states that if two players make the same contribution to any nonempty coalition, then they receive the amounts in proportion to their stand-alone worths. We characterize the family of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
2
2
0
Order By: Relevance
“…This family of values is in line with a recent and growing literature that combine different allocation principles by considering convex combinations of two extreme values, such as the egalitarian Shapley values (being convex combinations of the Shapley value and equal division value, see Joosten (1996) and van den Brink et al (2013)), the consensus values (being convex combinations of the Shapley value and equal surplus division value, see Ju et al (2007)) and the family of convex combinations of the equal division value and the equal surplus division value (axiomatized in, e.g., van den Brink and Funaki (2009); van den Brink et al (2016); Xu et al (2015); Ferrières (2017)). Also, our family of values is in line with a recent and growing literature on non-symmetric surplus sharing values, such as the weighted division value (Béal et al, 2015(Béal et al, , 2016a, the weighted surplus division value Llerena, 2017, 2019), the weighted equal allocation of non-separable contributions value (Hou et al, 2019), and the PD value (Zou et al, 2019).…”
Section: Introductionsupporting
confidence: 55%
“…This family of values is in line with a recent and growing literature that combine different allocation principles by considering convex combinations of two extreme values, such as the egalitarian Shapley values (being convex combinations of the Shapley value and equal division value, see Joosten (1996) and van den Brink et al (2013)), the consensus values (being convex combinations of the Shapley value and equal surplus division value, see Ju et al (2007)) and the family of convex combinations of the equal division value and the equal surplus division value (axiomatized in, e.g., van den Brink and Funaki (2009); van den Brink et al (2016); Xu et al (2015); Ferrières (2017)). Also, our family of values is in line with a recent and growing literature on non-symmetric surplus sharing values, such as the weighted division value (Béal et al, 2015(Béal et al, , 2016a, the weighted surplus division value Llerena, 2017, 2019), the weighted equal allocation of non-separable contributions value (Hou et al, 2019), and the PD value (Zou et al, 2019).…”
Section: Introductionsupporting
confidence: 55%
“…This family of values is in line with a recent and growing literature that combine different allocation principles by considering convex combinations of two extreme values, such as the egalitarian Shapley values (being convex combinations of the Shapley value and equal division value, see Joosten (1996) and van den Brink et al (2013)), the consensus values (being convex combinations of the Shapley value and equal surplus division value, see Ju et al (2007)) and the family of convex combinations of the equal division value and the equal surplus division value (axiomatized in, e.g., van den Brink and Funaki (2009);van den Brink et al (2016); Xu et al (2015); Ferrières (2017)). Also, our family of values is in line with a recent and growing literature on non-symmetric surplus sharing values, such as the weighted division value (Béal et al, 2015(Béal et al, , 2016a, the weighted surplus division value Llerena, 2017, 2019), the weighted equal allocation of non-separable contributions value (Hou et al, 2019), and the PD value (Zou et al, 2019).…”
Section: Introductionsupporting
confidence: 55%
“…It is shown that the affine combinations of the ED and ESD values can be characterized using projection consistency by van den Brink et al (2016). Zou et al (2019) use projection consistency to characterize the PD value. Several values satisfy projection consistency, see, e.g., Funaki and Yamato (2001); Llerena (2017, 2019).…”
Section: Consistencymentioning
confidence: 99%
“…Undoubtedly, an extreme egalitarian value is the equal division value (characterized in van den Brink (2007)), which allocates the total worth equally among all players. As an alternative to this equality principle, the proportional division value (Zou et al, 2019) relies on the proportionality principle: it gives payoffs in proportion to players' stand-alone worth.…”
Section: Introductionmentioning
confidence: 99%